Dipeptidyl peptidase-4 inhibitor anagliptin facilitates restoration of dextran sulfate sodium-induced colitis. (1st October 2013) - Mimura, Shunya; Ando, Takafumi; Ishiguro, Kazuhiro; Maeda, Osamu; Watanabe, Osamu; Ujihara, Masaki; Hirayama, Yutaka; Morise, Kazuhiro; Maeda, Keiko; Matsushita, Masanobu; Funasaka, Kohei; Nakamura, Masanao; et al.
Abstract: Objective. Inflammatory bowel disease (IBD) is a chronic debilitating disease associated with severe damage to the intestinal mucosa. Glucagon-like peptide-2 (GLP-2) is a potent and specific gastrointestinal growth factor. GLP-2 released from enteroendocrine cells is inactivated by dipeptidyl peptidase-4 (DPP-4). The aim of this study was to examine whether the DPP-4 inhibitor anagliptin improves experimental murine colitis. Material and methods. Male C57BL/6 mice aged 8 weeks were exposed to 1.5% dextran sulfate sodium (DSS) in drinking water for 7 days to induce experimental colitis. Anagliptin (0.1% in diet) was administrated from 2 days before the beginning of DSS to 7 days after the end of DSS. Changes in body weight and disease activity index were evaluated daily. Histological colitis severity, cellular proliferation and gene expression were determined in colonic tissues. Results. Treatment with anagliptin clearly improved body weight loss and disease activity index in the recovery phase. Histological score in the DSS + anagliptin group at day 14 was significantly lower than that in the DSS alone group. Treatment with anagliptin increased the Ki67-positive rate at days 10 and 14, and tended to increase insulin-like growth factor-1 mRNA expression in the DSS + anagliptin group. Conclusion. In this model of experimental colitis, the DPP-4 inhibitor anagliptin facilitated the restoration of mucosal damage, thereby resulting in the acceleration of healing. These findings suggest a new and novel therapeutic approach for the treatment of IBD.